COMPARISON OF THE MICRO-SIMULATION SOFTWARE AIMSUN & IHCM-1997 FOR HIGHWAY TRAFFIC PERFORMANCE ANALYSIS - Aji Ronaldo (Journal of the Civil Engineering Forum, 2012)
In order to make good decisions in transportation, decision-makers need some references to support it. One of the sources for such reference is by performing a micro-simulation; a model for representing real-world conditions including the behavior of travelers, vehicles and the infrastructure. This study examines and presents a comparison between AIMSUN (a commercial micro-simulation software) and Indonesia Highway Capacity Manual 1997(IHCM-1997) in relation to the road traffic performance of the study object Södralänken, E266 and E75, in the southern part of Stockholm, Sweden. A calibration process was conducted in order to find the best value of a set of parameters in each software, selected based on the lowest value of a Root Mean Square Error (RMSE) computed based on observed speed data and the model output. The parameters were then validated using evening peak-hour data. The comparisons were conducted in terms of flow, speed and density by AIMSUN, IHCM-1997 and the observation data on morning and evening peak-hour. The results are from the given experiments with the AIMSUN software with the best set of parameters being when the value of Maximum Desired Speed is at 100 km/h and Speed Acceptance is at 1,1. It shows that the significant difference between AIMSUN, IHCM-1997 and observation lays on the speed. IHCM-1997 gives relatively higher speed than both AIMSUN and observation data.